STRATEGI PEMBELAJARAN MOTORIK KASAR BERBASIS METODE PSIKOTERAPI BAGI ANAK AUTIS PADA MASA PANDEMI COVID-19 - Abdul Rahim; Taryatman Taryatman; Endang Hangestiningsih (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2020)
This study aimed to describe gross motor learning strategies through psychotherapy methods for autistic children during the COVID-19 pandemic. The research method used was descriptive qualitative. The data collection techniques employed were observation, interview and documentation. This research was located at SD Taman Muda Ibu Pawiyatan Yogyakarta City with the research subjects of low grade autistic students. The results of the research on students with special needs at SD Taman Muda Ibu Pawiyatan showed: (1) The gross motor learning strategy through the psychotherapy method was carried out through the principle of playing by creating a sense of pleasure and ensuring safety. (2) Train gross motor responses through playing to improve the emotional relationship between parents and children, (3) Train visual-motor interactions through playing activities to increase children's visual responses. During the COVID-19 pandemic, parents were required to replace the roles of teachers and therapists. Children's activities needed to be fully supported by parents. Parent must make sure that the child's health condition was good enough. If the child had a fever, delayed it until the child is recovered or the child's self-immune was optimal.